2018
DOI: 10.1111/twec.12746
|View full text |Cite
|
Sign up to set email alerts
|

Comparing approval procedures for new drugs

Abstract: K E Y W O R D Saccess to new drugs, drug approval, international reference pricing 1 | INTRODUCTION This paper analyses how drug approval procedures influence the incentives of pharmaceutical firms to commercialise new drugs in different countries under international reference pricing. The general focus is on the exogenous timing of drug approvals, the endogenous choice of countries for the launches of new drugs and the regulated pricing of drugs. We also analyse in a simple framework the preferences of countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Houy and Jelovac [ 38 , 100 ] showed that their application may delay listing in some countries, while Bardey et al [ 33 ] pointed out that they may reduce expenditure in R&D. Finally, Voehler et al [ 101 ] showed that the price itself does not seem to change dramatically as a result of this regulation. The issue of investment in innovation is certainly very important as pricing may change the timing of the launch of new technologies and the return on investment in innovative drugs [ 100 , 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Houy and Jelovac [ 38 , 100 ] showed that their application may delay listing in some countries, while Bardey et al [ 33 ] pointed out that they may reduce expenditure in R&D. Finally, Voehler et al [ 101 ] showed that the price itself does not seem to change dramatically as a result of this regulation. The issue of investment in innovation is certainly very important as pricing may change the timing of the launch of new technologies and the return on investment in innovative drugs [ 100 , 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…. 17 In the North, welfare increases in the reimbursement limit. A (potential) decrease in the reimbursement limit increases the consumer copayment for a given drug price 18 and decreases the quantity demanded.…”
Section: No Parallel Trade (X; ?R; X; Rr)mentioning
confidence: 99%
“…The e¤ect of parallel trade on regulation is linked to the policy issue of access to pharmaceuparallel trade may result in greater launch delays. Also, approval procedures for new drugs and approval times may contribute to non-launches (Houy & Jelovac, 2019). ticals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By changing regulatory decisions in destination and/or source country of parallel imports, parallel trade may result in regulatory convergence or regulatory divergence. In the former contribute to non-launches (Houy & Jelovac, 2018). case, parallel trade may also erode price di¤erences between countries, in particular, if price di¤erences are regulation driven.…”
Section: Introductionmentioning
confidence: 99%